ANALISIS HADHANAH PADA PUTUSANHADHANAHPENGADILANAGAMA MEDAN(STUDI PUTUSAN PENGADILAN AGAMA MEDAN) TAHUN 2010-2012 - NIRMAYANI LAKSANI PUTRI PULUNGAN (PREMISE LAW JURNAL, 2014)
ABSTRACT By the ending of a marriage, based on the Court’ verdict which is final and conclusive, there will be followed by legal consequence; one of them is about Hadhanah (child custody) on children who are born from that marriage.The theory used in the research was the theory of legal certainty by Jan Michiel Otto, supported by the theory of benefit by Al-Ghazali. The research was conducted by using judicial normative method with descriptive analytic approach.It can be concluded that in accordance with Article 105 of the Compilation of Islamic Laws, the custody of children who are before mummayiz (having arrived at the age of discretion/reason) or under 12 years old is given to the mother, while the custody of children who are after mummayiz, it is up to them to choose one of their parents. However, it is not possible that children who are before mummayiz, hadhanah is given to the father if it is evidence that the mother is legally defective. Legal provisions which stipulate the protection for children’s rights, found in Law No. 4/1979 on the Welfare of Children, Law No. 23/2002 on the Protection for Children, and Law No. 39/1999 on Human Rights, are sufficient in regulating the protection and the welfare of children. This becomes judges’ consideration in giving a verdict about hadhanah dispute. In hadhanah dispute, specifically, the implementation of real executorial verdict is made involuntarily. Keywords: Hadhanah, Mummayiz.